FATORES DE SOLO E CLIMA QUE AFETAM O RENDIMENTO MÃ‰DIO DO MILHO NAS REGIÃ•ES HOMOGÃŠNEAS DA PARAÃBA - Rocha Filho, J. V. C.; Alcoforado, C. B.; Pessoa da Costa, G. T.; Tejeda, H. R. (REVISTA DE AGRICULTURA, 2020)
FATORES DE SOLO E CLIMA QUE AFETAM O RENDIMENTO MÃ‰DIO DO MILHO NAS REGIÃ•ES HOMOGÃŠNEAS DA PARAÃBA